The Role of Religious and Ethical Values in Preventing the Influence of LGBT Among Adolescents at State Vocational School 1 Cikampek - Salma Gania; Ratu Nikita Ristanti; Ahmad Farhan Mulyadi; Oyoh Bariah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the role of religious values in shaping adolescents' character in facing negative influences, particularly LGBT, in both the school and family environments. The methods used in this research include in-depth interviews with Mr. Wawan Iwank Kurniawan, an Islamic Religious Education teacher at SMKN 1 Cikampek, and direct socialization to students in the classroom to enhance their understanding of the importance of religious values in dealing with such social issues. The findings indicate that religious values such as faith, worship, and morality play a crucial role in shaping adolescents' character. Parents, as the